#### (i) (8/125)^{-1/3}

**Solution:**

(8/125)^{-1/3}

= [(2 x 2 x 2)/(5 x 5 x 5)]^{-1/3}

= (2^{3}/5^{3})^{-1/3}

= (2/5)^{3 x -1/3}

= (2/5)^{-1}

= 5/2 = 2½

#### (ii) (0.027)^{-1/3}

**Solution:**

(0.027)^{-1/3}

= (27/1000)^{-1/3}

= [(3 x 3 x 3)/(10 x 10 x 10)]^{-1/3}

= (3^{3}/10^{3})^{-1/3}

= (3/10)^{3 x -1/3}

= (3/10)^{-1}

= 10/3

**More Solutions:**

- Evaluate for the following indices:
- Simplify for the following indices:
- Solve Indices:
- Solve the following : (i) (a-1 + b-1) ÷ (a-2 – b-2)
- Prove the following: (i) (a + b)-1 (a-1 + b-1) = 1/ab
- If a = cz, b = ax and c = by, prove that xyz = 1.
- Prove that aq – r. br – p. cp – q = 1.
- Prove that 1/x + 1/y + 1/z = 0.
- Prove that x = 2yz/y – z.